PARTICIPATION OF GOVERNMENT AGENCIES IN TOURISM MANAGEMENT NAKHON PHANOM PROVINCE FROM SECONDARY CITIES TO MAIN CITIES - Jandang, Pasit; Wised, Samran; Inthanon, Worawut (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
The objectives of this research were 1) the level of participation of government agencies in tourism management in Nakhon Phanom Province, from secondary cities to main cities, 2) the level of factors affecting the participation of government agencies in tourism management in Nakhon Phanom Province, from secondary cities to main cities, and 3) the factors affecting the participation of government agencies in tourism management in Nakhon Phanom Province, from secondary cities to main cities. The sample consisted of 378 participants using Yamane Taro's formula. The instrument used was a set of questionnaires with a reliability of .94. Data were analyzed through frequency distribution, percentage, mean, standard deviation, Pearson's product-moment correlation coefficient, and multiple regression analysis. The research results found that: 1) The level of participation of government agencies in tourism management in Nakhon Phanom Province, during the transition from secondary cities to main cities, was at a moderate level. Considering each aspect, participation in benefits, operations, and decision–making was also moderate; 2) The factors affecting the government agencies’ participation in tourism management in Nakhon Phanom Province, during the transition from secondary cities to main cities, were overall at a moderate level. These factors were motivation, communication, and organizational culture; and 3) The factors affecting the government agencies’ participation in tourism management in Nakhon Phanom Province, during the transition from secondary cities to main cities, using Pearson's product-moment correlation coefficient statistics, showed a moderate relationship at the .05 level of significance